2019
DOI: 10.1007/s00259-019-04643-7
|View full text |Cite
|
Sign up to set email alerts
|

The management impact of 68gallium-tris(hydroxypyridinone) prostate-specific membrane antigen (68Ga-THP-PSMA) PET-CT imaging for high-risk and biochemically recurrent prostate cancer

Abstract: Purpose To determine the impact on clinical management of patients with high-risk (HR) prostate cancer at diagnosis and patients with biochemical recurrence (BCR) using a new kit form of 68 Ga-prostate-specific membrane antigen (PSMA), namely tris(hydroxypyridinone) (THP)-PSMA, with positron emission tomography-computed tomography (PET-CT). Methods One hundred eighteen consecutive patients (50 HR, 68 BCR) had management plans documented at a multidisciplinary meeting before 68 Ga-THP-PSMA PET-CT. Patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…prospectively investigated 50 patients with high-risk PCa. Of the 50 patients, 12 (24%) had management changed after PSMA PET/CT imaging ( 16 ). Hofman et al.…”
Section: Discussionmentioning
confidence: 99%
“…prospectively investigated 50 patients with high-risk PCa. Of the 50 patients, 12 (24%) had management changed after PSMA PET/CT imaging ( 16 ). Hofman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Francolini et al also found that a short time to PSA relapse (2.5 years) increased the rate of positive sites in 68 Ga-PSMA PET/CT findings [ 51 ]. Kulkarni et al showed that patients with a high ISUP grade and a short PSADT had a high rate of 68 Ga-PSMA PET/CT positive findings [ 52 ]. Additionally, a previous meta-analysis reported that a short PSADT at PSA relapse predicted many positive sites on 68 Ga-PSMA PET/CT [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled data of all patients included in this review show an overall change of management in 861 of 1899 patients (45%). Nine studies, including 729 patients, reported sufficient data to extract the kind of change in management [20,24,26,27,29,33,36,38,40]. In 332 (46%) of these 729 patients a change in management was seen.…”
Section: Resultsmentioning
confidence: 99%